2016
DOI: 10.1007/s11894-016-0506-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer: How Can We Reduce the Incidence of this Disease?

Abstract: Gastric cancer remains a prevalent disease worldwide with a poor prognosis. Helicobacter pylori plays a major role in gastric carcinogenesis. H. pylori colonization leads to chronic gastritis, which predisposes to atrophic gastritis, intestinal metaplasia, dysplasia, and eventually gastric cancer. Screening, treatment, and prevention of H. pylori colonization can reduce the incidence of gastric cancer. Other interventions that may yield a similar effect, although of smaller magnitude, include promotion of a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 64 publications
0
98
1
2
Order By: Relevance
“…7 Smoking and alcohol are also risk factors for GC. 11 However, in the present study, no correlation between a positive history of smoking or alcohol consumption and the incidence of synchronous GC in patients with HNSCC was shown and it might be attributed to the too low number of patients with synchronous GC. A previous study showed that synchronous esophageal SCC was detected in patients with HNSCC located in the pharynx and hypopharynx.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…7 Smoking and alcohol are also risk factors for GC. 11 However, in the present study, no correlation between a positive history of smoking or alcohol consumption and the incidence of synchronous GC in patients with HNSCC was shown and it might be attributed to the too low number of patients with synchronous GC. A previous study showed that synchronous esophageal SCC was detected in patients with HNSCC located in the pharynx and hypopharynx.…”
Section: Discussioncontrasting
confidence: 83%
“…8 Histologically, most GCs are adenocarcinoma, and the risk factors for GC are Helicobacter pylori infection and certain life habits, such as salty diet, smoking, and alcohol consumption. 11 GC is the second most common cancer in Korea followed by thyroid carcinoma; 10 however, the incidence of synchronous GC in patients with HNSCC has not been reported to date. In the present study, we investigated the incidence of synchronous GC …”
mentioning
confidence: 99%
“…Non-cardia intestinal adenocarcinomas probably develop via a specific pathway that starts with chronic gastritis, which leads to gland loss, development of atrophic gastritis, intestinal metaplasia and dysplasia culminating in gastric adenocarcinoma15 (table 1). Apparently, infection of H. pylori is not the only determinant of gastric cancer incidence and other factors play an important role 16. In the current review, we will discuss the recent advances in our understanding of the molecular events that cause gastric cancer and the new emerging targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Like other solid malignancies of gastrointestinal origin, gastric cancer is curable when diagnosed in its early stage of development . Given its population's high incidence of GC and the life‐saving benefit of early detection, South Korea's National Cancer Screening Program recommends screening by upper endoscopy (UE) or upper gastrointestinal (UGI) series every other year starting at 40 years of age . The endoscopic evaluation based on the stomach lining examination, alone or by combination with biopsy, can help predict risks and guide therapeutic intervention .…”
Section: Introductionmentioning
confidence: 99%